2011
DOI: 10.1039/c1cp21252d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics effects on luminescence properties of oligothiophene derivatives: a molecular mechanics–response theory study based on the CHARMM force field and density functional theory

Abstract: CHARMM force field parameter values for a class of oligothiophene derivatives have been derived with reference to density functional theory/B3LYP potential energy surfaces. The force field parametrization of these luminescent conjugated polyelectrolytes includes the electronic ground state as well as the strongly light absorbing first excited state. In conjunction with quantum chemical response theory calculations of transition state properties, a molecular dynamical model of the Stokes shift is obtained. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…Owing to low torsional barriers in the excited state (< k B T), the conformational change in structure S3 B can be induced by thermal energy, which results from repeated excitation laser pulses. [34][35][36] In accordance with these results, the constructed fluorescence-lifetime distributions of compound S3, with the fitted fluorescence lifetime at the first and second emissive levels, show bimodal features, as shown in Figure 4 a. The distributions are fitted by two Gaussian functions with mean values of 410 ps and 1.41 ns.…”
Section: Stokes Shiftsupporting
confidence: 80%
See 1 more Smart Citation
“…Owing to low torsional barriers in the excited state (< k B T), the conformational change in structure S3 B can be induced by thermal energy, which results from repeated excitation laser pulses. [34][35][36] In accordance with these results, the constructed fluorescence-lifetime distributions of compound S3, with the fitted fluorescence lifetime at the first and second emissive levels, show bimodal features, as shown in Figure 4 a. The distributions are fitted by two Gaussian functions with mean values of 410 ps and 1.41 ns.…”
Section: Stokes Shiftsupporting
confidence: 80%
“…[34][35][36] In accordance with these results, the constructed fluorescence-lifetime distributions of compound S3, with the fitted fluorescence lifetime at the first and second emissive levels, show bimodal features, as shown in Figure 4 a. In the expected structure of conformer S3 B, the innermost thiophene ring of one conjugated thiophene arm is almost orthogonally attached to the plane of the phenyl core, whilst the other innermost thiophene rings of two arms are in the same plane as the core.…”
Section: Stokes Shiftsupporting
confidence: 78%
“…The fluorescence decay time of neat p‐FTAA in deionized water was recently determined to be around 600 ps and upon binding to recombinant amyloid fibrils the decay time was increased to around 800 ps 22, 25. Using the same excitation, 403 nm, p‐FTAA‐porph in water displayed decay times around 680 ps for the green p‐FTAA emission ( λ = 540 nm), but considerably longer, 1600 ps and 1900 ps, for porphyrin assigned emission at λ = 595 nm and λ = 640 nm (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We have applied the established calculation software named NAMD package 52) with the CHARMM 22 [53][54][55][56] for simulating molecular interaction between A1 domain of VWF and N-terminus domain of GPIb . By Monte-Carlo simulation, we have previously shown that the localization GPIb is a key determinant factor for platelet binding with large size of VWF molecule 57) .…”
Section: Lrr5mentioning
confidence: 99%